Breast cancer in Poland – the urgent need for effective prevention - Ciuba, Amelia (Family Medicine & Primary Care Review, 2024)
Breast cancer is the dominant health problem in the female population. In 2020, it was responsible for 23.8% of cancer cases and 15.3% of cancer-related deaths. In the total number of female malignancies, the share of breast cancer is constantly increasing, with the growth rate reaching about 2.2% per year. The risk of breast cancer increases with age, genetic factors, family history, hormonal factors, and lifestyle. Research in the field of psychoneuroimmunology demonstrates the existence of a bidirectional relationship between the nervous and immune systems. Psychological factors that may increase the risk of breast cancer incidence include chronic stress, feelings of helplessness, suppression of emotions (especially anger), external locus of control, anxiety, and depression. The nature of breast cancer symptoms depends on the stage. In the case of this disease, the initial stage is asymptomatic, and any cancerous changes can only be detected during preventive mammography. Early detection and medical intervention greatly increase the chances of a cure. The biggest challenge for the healthcare system is late diagnosis. Identification of the factors affecting women’s participation in population-based screening may allow for tailoring health education to the recipient, increasing women’s attendance in mammography examinations, and improving the effectiveness of preventive programs, thus reducing breast cancer mortality in the population of Polish women.